2009
DOI: 10.2136/vzj2008.0038
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Multifractal Features of Soil Particle Size Distributions with Kolmogorov Fragmentation Algorithms

Abstract: We have developed a new type of fragmentation algorithm that was inspired by a theoretical question raised by A.N. Kolmogorov—and still unanswered after 60 yr—regarding the characteristics of fragment size distributions when the size of the fragments, rβ, exhibits a power‐law dependence on the size of the original material, r, with 0 ≤ β ≤ 1. Our fragmentation algorithm uses β and N (which denotes the number of particles produced in the fragmentation) as input parameters and was used for various simulations pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…It is observed that the influence of the random component diminishes for increasing number of points used in the simulation. Also the Table 3 2 0,5-0,5-0,5-0, 5 1,991 0,9999 0,25-0,25-0,25-0,25 0,7-0,7-0,5-0,5 1,951 0,9999 0,8-0,6-0,7-0, 6 1,924 0,9997 2 values become closer to 1. Figure 4 shows the value of the estimated entropy dimension for increasing number of points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the influence of the random component diminishes for increasing number of points used in the simulation. Also the Table 3 2 0,5-0,5-0,5-0, 5 1,991 0,9999 0,25-0,25-0,25-0,25 0,7-0,7-0,5-0,5 1,951 0,9999 0,8-0,6-0,7-0, 6 1,924 0,9997 2 values become closer to 1. Figure 4 shows the value of the estimated entropy dimension for increasing number of points.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this paper is providing a consistent explanation of the mentioned results via an extremely simple model. Recently fragmentation algorithms were proposed to replicate the multifractal nature of soil PSD (Martín et al [6]). In…”
mentioning
confidence: 99%
“…As previously stated, different multifractal parameters represent different information for soil PSDs. High values of these multifractal parameters indicate that PSDs have wide ranges, high heterogeneities, and are more homogeneous among all intervals [21,43,44]. Increases in multifractal parameters may be attributed to increases in fine-soil particles [40,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Bird et al (2009) present a generalization of Turcotte's (1986) fractal fragmentation model by introducing a time component and relaxing the requirement for a single scale-invariant probability of failure. Martín et al (2009) show how an extension of Kolmogorov's (1941) fragmentation theory can generate multifractal mass-size distributions. One of the missing links in this special section is the connection between soil fragmentation and pore space geometry, that is, packing models.…”
Section: Fractal and Mul Fractal Models Applied To Porous Mediamentioning
confidence: 96%
“…Next, Bird et al (2009) and Martín et al (2009) introduce some new mathematical approaches for modeling the dynamic fragmentation of earth materials. Bird et al (2009) present a generalization of Turcotte's (1986) fractal fragmentation model by introducing a time component and relaxing the requirement for a single scale-invariant probability of failure.…”
Section: Fractal and Mul Fractal Models Applied To Porous Mediamentioning
confidence: 99%